Pendapat Siswa tentang Pelaksanaan Layanan Konseling Kelompok - Suryani, Suryani; Khairani, Khairani (Universitas Negeri Padang, 2013)
Â Abstract: Group counseling is a service that helps alleviate the problems experienced by the learners through group dynamics in order to achieve optimal growth.Reality on the ground that the process implementation counseling services the group have not been effective in helping alleviating the problems siswa.Tujuan research describe students' opinions about the implementation of counseling services group be seen from time the implementation, stage the implementation, the role of group leader, the role members of the group and the achievement objectives counseling services the group. Types of descriptive research, with the findings the research, opinions students about the implementation of counseling services group in SMAN 6 Padang runs with well.Keyword: Opinion; Group CounselingÂ